Rental Flexibility over Sharia Compliance: Musyarakah Mutanaqishah Property Financing for Indonesian Millennials - Mohammad Taqiyuddin Bin Mohammad; Taufiq Ramadhan; Zulfikar Yahya Anhar; Atika Uwaida; Rafli Gunawan (Ethiconomics: Journal of Islamic Banking and Finance, 2026)
The growing demand for sharia-compliant property financing among the millennial generation has positioned Musyarakah Mutanaqishah (MMQ) as a strategic contract within Islamic banking. However, the practical implementation of MMQ in Indonesia continues to face challenges related to sharia compliance, contract structure rigidity, and limited adaptability to digital financial behaviors of younger consumers. This study aims to: First, examine the level of sharia compliance in the implementation of MMQ contracts at Indonesian Islamic banks, Second, identify innovations needed to enhance MMQ relevance for millennial customers; and Third, analyze the determinants of millennial preferences toward MMQ-based property financing. The research employs a sequential mixed-methods design, combining qualitative content analysis of MMQ contract documents from five major Islamic banks with a quantitative survey of 412 millennial respondents (aged 25-40) across five major Indonesian cities, analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings reveal that: (1) sharia compliance scores ranged from 72.4% to 88.6%, with critical issues identified in the rental pricing mechanism (ujrah) and the proportional risk distribution; (2) digital integration, contract transparency, and rental flexibility significantly influence millennial preferences (β = 0.412, p < 0.001; β = 0.327, p < 0.001; β = 0.285, p < 0.001 respectively); and (3) religiosity moderates the relationship between sharia compliance perception and intention to use MMQ products. This study contributes to the Islamic finance literature by proposing an Integrative MMQ Innovation Framework that synthesizes sharia governance, digital transformation, and generational preferences. Practical implications are offered for Islamic banks, regulators (DSN-MUI, OJK), and Sharia Supervisory Boards to design more adaptive and compliant MMQ products for the millennial market.